Einfluss einer reduzierenden Atmosphäre auf die Materialeigenschaften oxidischer Feuerfestwerkstoffe. Issue 10 (8th July 2014) - Gehre, Patrick; Aneziris, Christos G.; Gutte, Heiner
<x xml:space="preserve">Abstract</x> The gasification technology is a key process of the chemical and energy industry. In order to improve the efficiency and environmental sustainability of the gasification plant, the impact of the sintering atmosphere on the thermo‐mechanical properties, the thermal shock resistance as well as the phase composition of alumina, Al2O3‐ZrO2‐TiO2, MgAl2O4 and CA6 was investigated and compared. The gained results present a powerful tool for operators of a gasification plant for the choice of suitable new refractory materials.